Impact of low molecular weight organic acids (LMWOAs) on biochar micropores and sorption properties for sulfamethoxazole. (July 2016) - Sun, Binbin; Lian, Fei; Bao, Qiongli; Liu, Zhongqi; Song, Zhengguo; Zhu, Lingyan
Abstract: The interaction between biochar (BC) and antibiotics with the presence of low molecular weight organic acids (LMWOAs) is largely unknown, although it is crucial for understanding the role of BC in reducing the bioavailability of antibiotics in rhizosphere. The impacts of two typical LMWOAs (citric and malic acids) on sorption of sulfamethoxazole (SMX) by crop-straw BCs produced at 300 °C (BCs300) and 600 °C (BCs600), respectively, were examined. The sorption of SMX on BCs increased more than 5 times with the concentration of LMWOAs increasing from 0 to 100 mmol/L, which was mainly attributed to the elevated microporosity of BCs (measured by CO2 ) after treated by LMWOAs. The pore development of BCs was mainly derived from the release of dissolved organic residues from BC by LMWOA washing. For H2 O2 -oxidized BCs, however, LMWOAs had little effect on SMX sorption by BCs300 but greatly increased that by BCs600, which can be explained by the distinct sorption mechanisms of SMX on BCs300 and BCs600. These results indicate that the impact of LMWOAs on SMX sorption is highly dependent on the properties of BCs and LMWOAs, as well as their interaction mechanisms. Highlights: LMWOAs greatly enhanced the sorption of SMX on biochar. Elevated porosity of LMWOA-modified biochar was responsible for its increased sorption for SMX. LMWOAs facilitated the release of dissolved organic residues from bulk biochar. The release of dissolved organic residues contributed to the increased surface area and porosity. LMWOAs have distinct impacts on sorption properties of original and oxidized biochars. Abstract : Elevated porosity of biochar after washed by LMWOAs accounts for its increased sorption for SMX.